IMPROVING SIMPLE CONVERSATION ABILITY IN LEARNING INDONESIAN LANGUAGE IN CLASS II THROUGH THE USE OF WORD CARDS AT SD INPRES BUMI SAGU - Muh Rizal; Ni Gusti Nyoman Sriayuni; Sin Dinayanti Laudea (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to improve the simple conversation skills of class IIA students of SD Inpres Bumi Sagu through word card media in learning. The study was conducted using a classroom action research (CAR) method consisting of two cycles. Data were collected through observation and interviews, then analyzed descriptively to measure the improvement of students' simple conversation skills. Data collection was carried out by analyzing qualitative and quantitative data from observation sheets and interviews during the learning process. The success indicators were set with a target of 80% completion. The results showed that there was a significant increase in all indicators after the application of word card media. The average value of students' simple conversation skills increased from 53% in the pre-cycle stage to 71% in cycle I, and reached 90% in cycle II. This increase shows that word card media can improve and enhance various aspects of students' conversation/speaking skills, especially in terms of clarity of articulation, fluency of speech, and understanding of the response of the interlocutor. Based on these findings, it is recommended that word card media be used more often in language learning to improve students' speaking skills. In addition, continuous practice and providing constructive feedback are essential to maximize learning outcomes.